Fine‐needle aspiration of adrenal lesions: A 20‐year single institution experience with comparison of percutaneous and endoscopic ultrasound guided approaches. Issue 10 (21st June 2019) - Novotny, Aaron G.; Reynolds, Jordan P.; Shah, Akeesha A.; Bhatt, Amit; Chahal, Prabhleen; Remer, Erick M.; Stevens, Tyler; Gmitro, Stephen; Sturgis, Charles D.
Abstract: Background: Historically, sampling of adrenal lesions has been performed by percutaneous image‐guided fine‐needle aspiration (FNA) biopsy. Endoscopic ultrasound guided (EUS)‐FNA of the adrenals was first employed at Cleveland Clinic ~10 years ago. We report a two‐decade experience of adrenal FNA in our institution. Methods: An electronic retrieval identified adrenal FNAs from 1997 to 2017. Data points from each case (diagnosis, method of FNA, age, sex, laterality, needle gauge, size of lesion, adequacy of sample, and histologic follow up) were analyzed. Results: Our retrieval confirmed 198 adrenal FNAs performed over 20 years. Of these, 90% (179/198) were percutaneous, and the remaining 10% (19/198) were collected by EUS. Of the 179 CT guided FNAs, 93% (162/179) yielded an adequate specimen as compared with an adequacy rate of 89% (17/19) for EUS‐FNAs, with no significant difference in adequacy rates by collection method, P = .64 (Fisher's exact). Of all adrenal FNAs, 53% (105/198) confirmed metastases, 33% (65/198) showed adrenal cells or primary adrenal neoplasms (85% cortical cells, 14% cortical neoplasia, 1% pheochromocytoma), 8% were inadequate (15/198), 3% were atypical (7/198), and 2% were suspicious for malignancy (5/198). Conclusion: FNA of the adrenal glands can be useful in the diagnosis and staging of metastatic neoplasms, as well as in distinguishing primary adrenal cortical from medullary neoplasms and characterizing hematolymphoid and mesenchymal neoplasms. Overall adequacy rates for adrenal cytology are high (92%) with no statistically significant difference between CT‐guided (93%) and EUS‐FNA adequacy (89%). The majority of our procedures confirmed metastases, sparing patients unnecessary surgery.